1995
DOI: 10.1177/008124639502500105
|View full text |Cite
|
Sign up to set email alerts
|

AIDS-Risk among Street Children and Youth: Implications for Intervention

Abstract: With the co-operation of staff and volunteers from non-governmental programmes in nine South African cities, focus group discussions were held with 141 street children and youth, 79 of whom were enrolled in shelter programmes while 62 were still living independently on the streets. The group discussions focused on knowledge about transmission and prevention, attitudes towards AIDS and people with AIDS, and sexual and other behaviours related to AIDS risk. Both quantitative and qualitative information on the to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 20 publications
0
10
0
1
Order By: Relevance
“…Richter and Swart-Kruger (1995) indicate that the need for money, protection and intimacy are frequent influences in the sexual decision making of street children. Much of their research highlights the importance of power relationships in the sexuality of young people, yet this is also the case in less marginalised groups of adolescents.…”
Section: Macphailmentioning
confidence: 99%
“…Richter and Swart-Kruger (1995) indicate that the need for money, protection and intimacy are frequent influences in the sexual decision making of street children. Much of their research highlights the importance of power relationships in the sexuality of young people, yet this is also the case in less marginalised groups of adolescents.…”
Section: Macphailmentioning
confidence: 99%
“…Similarly, May et al, (2000) examined the challenges faced by South African youth as they matured in a society characterised by high rates of HIV/AIDS. Studies among homeless youth and street children, who represent particularly high risk groups, revealed dangerous constructions of sexuality which encompassed survival sex, rape and relationship sex on the streets (Richter et al, 1994;Richter and Swart-Kruger, 1995;SwartKruger and Richter, 1997). Although these surveys were directed primarily towards knowledge, attitudes and practices, these authors concluded that HIV/AIDS prevention could not be achieved without reflections on the wider context of sexuality (Swart-Kruger and Richter 1997).…”
Section: South African Studiesmentioning
confidence: 99%
“…With the advent of the AIDS pandemic (which in Africa is transmitted mainly through heterosexual sexual activity), attention has turned to sexual behaviour as an important factor in the fight to contain the disease. Of particular concern has been the behaviour of adolescents and young adults, as this group is acknowledged to be highly vulnerable to HlV infection (Richter & Swart-Kruger, 1995). Considerable research has focused on factors affecting condom use (Bandawe & Foster, 1996;Miles, 1992;Nicholas, 1998), exploring knowledge and beliefs about AIDS (Nicholas & Durrheim, 1995;Nicholas, Tredoux, & Daniels, 1994), and factors contributing to risk behaviours (Lindegger & Wood, 1995).…”
mentioning
confidence: 99%